Optimization of web-based physics learning technology through on-demand microlearning video download facility in an internet accessibility variation case - Henry Praherdhiono; Yulias Prihatmoko (Momentum: Physics Education Journal, 2023)
The research aims to see effectiveness through the perception of optimized physics learning web design through the development of on-demand microlearning video download facilities in diverse areas and access devices. Physics learning through web design, despite success in a variety of online learning methods, has major constraints on personalized learning. Individually, students have a variety of access devices and are in areas with a variable learning environment topology towards internet access. Agile development methods were developed to develop on-demand video download features on the physical learning web, and the development results were tested on MI-Ar Raudhah students based on characteristic compatibility. The development of the on-demand and simplified physical learning video download feature using microlearning is very effective for accessing students with varied Internet access devices and topologies.